INFLATIONARY DYNAMICS AND CAUSAL NEXUS OF BUDGETARY GAPS AND MONETARY EXPANSIONS: A TIME SERIES ANALYSIS WITH ARDL MODELLING FOR BANGLADESH (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
This paper examines the causal relationships  between inflation, budget deficit, and money  supply in Bangladesh from 1980 to 2023 using  the Autoregressive Distributed Lag (ARDL)  approach. Short-run causality analysis reveals  unidirectional influences from budget deficits  and money supply to inflation. Contrary to  common conjectures that link budget deficits  to inflation through increased money supply,  our findings reveal no causality between money  supply and inflation in both the short-run  and long-run. The study contributes to the  empirical literature by focusing on the unique  economic context of Bangladesh, which has  not been extensively explored in this tri variate relationship. The results suggest that  conventional economic theories may not fully  apply to developing countries like Bangladesh,  where monetary expansions do not necessarily  lead to inflationary pressures in the long run. The  paper concludes with policy recommendations based on the analysis of the ARDL model and  diagnostic tests confirming the model’s stability.
Keywords: Inflation; Budget Deficit; Money Supply; ARDL Model; Causality Analysis JEL Codes; C32; E31; E52; H62